Trends in Characteristics of Adults Enrolled in Traditional Fee-for-Service Medicare and Medicare Advantage, 2011–2019. Issue 3 (5th March 2022) - Weeks, William B.; Cao, Stacey Y.; Smith, Jeremy; Wang, Huabo; Weinstein, James N.
Abstract : Background: While overall Medicare Part C (Medicare Advantage) enrollment has grown more rapidly than fee-for-service Medicare enrollment, changes in the growth and characteristics of different enrollee populations have not been examined. Objectives: For 2011–2019, to compare changes in the growth and characteristics of younger (age younger than 65) and older (age 65 and older) Medicare beneficiaries enrolled in Medicare Part A only, Medicare Parts A & B, and Medicare Part C. Research Design: This was a retrospective, observational study. Subjects: Medicare beneficiaries who were alive and enrolled in Medicare Part A only, Medicare Parts A & B, or Medicare Part C on June 30 of each year and in no other plan that year. Measures: For each plan type and age group the numbers and mean ages of enrollees and the proportion of enrollees who were: black, female, concurrently enrolled in Medicaid, and (for older enrollees), whose initial reason for eligibility was old age and survivors' benefits. Results: Between 2011 and 2019, Medicare Part C experienced rapid expansions of 85.0% among older and 109.5% among younger enrollees. Part C enrollees were increasingly likely to be dually enrolled in Medicaid, Black and, among younger enrollees, female. Conclusions: Trends in demographic characteristics and changes in policy and growth in employer group plan offerings will likely continue to impact health care service utilization and costs in the Medicare population. Particularly as Medicare expansion to younger age groups is considered, future research should explore disparities in risk scores and care equity, quality, and costs across different Medicare enrollment options.